2003
DOI: 10.1080/cac.10.4-6.359.364
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Mutant Connexin 26 on Epidermal Differentiation

Abstract: To elucidate the mode of action of dominant mutant connexins in causing inherited skin diseases, transgenic mice were produced that express the true Vohwinkel syndrome-associated mutant Cx26 (D66H), from a keratin 10 promoter, specifically in the suprabasal epidermal keratinocytes. Following birth, the transgenic mice developed keratoderma similar to that of human carriers of Cx26 (D66H). Expression of the transgene resulted in a loss of Cx26 and Cx30 at intercellular junctions of epidermal keratinocytes and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…The G59A mutation causes a less severe palmoplantar hyperkeratosis and sensorineural deafness (22). Preliminary studies by Di et al (17) showed that D66H was retained within an unidentified intracellular compartment when expressed in HeLa cells and intracellular retained D66H was also observed in suprabasal keratinocytes in D66H transgenic mice (53). During the preparation of this manuscript, Marziano et al (54) reported that D66H and G59A mutations were both retained in a perinuclear localization; furthermore D66H exerted a dominant-negative effect on Cx26 but not Cx30, whereas G59A had a dominantnegative effect on Cx30 but surprisingly not on wild-type Cx26 (54).…”
Section: Discussionmentioning
confidence: 99%
“…The G59A mutation causes a less severe palmoplantar hyperkeratosis and sensorineural deafness (22). Preliminary studies by Di et al (17) showed that D66H was retained within an unidentified intracellular compartment when expressed in HeLa cells and intracellular retained D66H was also observed in suprabasal keratinocytes in D66H transgenic mice (53). During the preparation of this manuscript, Marziano et al (54) reported that D66H and G59A mutations were both retained in a perinuclear localization; furthermore D66H exerted a dominant-negative effect on Cx26 but not Cx30, whereas G59A had a dominantnegative effect on Cx30 but surprisingly not on wild-type Cx26 (54).…”
Section: Discussionmentioning
confidence: 99%
“…In this seminal study, the authors engineered a mouse that expressed the Cx26 D66H mutant driven by the keratin-10 promoter and that exhibited the mild to moderate sensorineural hearing loss and Vohwinkel syndrome (39). This mouse was viable and, notably, exhibited the hallmark keratoderma characteristics of patients that harbor this mutation and suffer from Vohwinkel syndrome.…”
Section: Mouse Models Of Connexin Diseasementioning
confidence: 99%
“…Although channel malformation is the most common feature of Cx26 and Cx43 mutants, a second class of mutants (e.g. Cx26 D66H (27) and Cx43 fs260 (25)) exhibit protein trafficking defects. In the case of the D66H mutant, it may still retain the capacity to reach the cell surface but fail to stabilize and return to the trans-Golgi network, where it is most prevalent (29).…”
Section: Expression Of Cx26 and Cx43 Mutants In Reference Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…This collection of studies has resulted in considerable debate as to how Cx26 is transported within mammalian cells during gap junction biogenesis. The importance of this debate has been elevated in recent years as it appears that the manifestation of human deafness in combination with etiologies of epidermal keratodermas depends extensively on the trans-dominant interactions of Cx26 mutants with other members of the connexin family (Bakirtzis et al, 2003;Forge et al, 2003;Marziano et al, 2003;Rouan et al, 2001;Thomas et al, 2004), possibly by co-oligomerization of the mutant with wild-type connexins while they co-reside within the same intracellular compartments. Likewise, the recent identification of Cx43 point mutations linked to oculodentodigital dysplasia (ODDD) (Paznekas et al, 2003;Richardson et al, 2004) has raised similar questions as to how Cx43 mutants may crosstalk with other members of the connexin family, including Cx26.…”
Section: Introductionmentioning
confidence: 99%